Analisis Potensi Daya Tarik Wisata Kuliner Sudirman Street Bandung - Rivan Akbar Putra Nurdiansyah; Nadia Karina; Harits Muflihussalam; Taufiq Hidayat (Manajemen dan Pariwisata, 2023)
Tourism plays an important role in supporting the economy of a region because it has a link in the economic growth of the region. Bandung city is one of the tourist destinations visited by many local and foreign tourists. As one of the cities that has a lot of tourism potential that can be developed. One of the culinary attractions in Bandung is Jalan Sudirman. The purpose of this study is to analyze the tourist attraction in culinary tourism in Jalan Sudirman. This study uses qualitative research methods based on the results of observation and literature review by describing the attractiveness of culinary tourism in Jalan Sudirman. The results of this study describe the motivation of tourists and culinary attractions in Jalan Sudirman.